Enriched Environment Prevents Surgery-Induced Persistent Neural Inhibition and Cognitive Dysfunction - Yang, Shana; Zhang, Song; Tang, Wenting; Fang, Shunchang; Zhang, Hongyang; Zheng, Jieyan; Liu, Xia; Zhang, Ying; Zhao, Liang; Huang, Lianyan; Li, Boxing (Frontiers in Aging Neuroscience, 2021)
Perioperative neurocognitive disorders (PND) encompass short-term delirium and long-term cognitive dysfunction. Aging increases the susceptibility to PND, yet the neural mechanism is not known. In this study, we monitored the dynamic changes of neuronal activity in the prelimbic cortex before and after surgery. We found that anesthesia combined with surgery, but not anesthesia alone, induced a prolonged decrease in neuronal activity during the post-operation period in the aged mice, but not in the adult mice. The prolonged decrease in neuronal activity was accompanied by surgery-induced microglia activation and proinflammatory cytokines expression. Importantly, we found that the enriched environment (EE) completely prevented both the prolonged neural inhibition and neuroinflammation, and improved cognitive function in the aged mice. These results indicate that the prolonged neural inhibition correlated to PND and that EE before the surgery could effectively alleviate the surgery- induced cognitive dysfunction.